2020
DOI: 10.3389/fmicb.2020.569700
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Human Milk Oligosaccharides on Growth of Bifidobacteria in Monoculture and Co-culture With Faecalibacterium prausnitzii

Abstract: Human milk oligosaccharides (hMOs) are important bioactive components in mother's milk contributing to infant health by supporting colonization and growth of gut microbes. In particular, Bifidobacterium genus is considered to be supported by hMOs. Approximately 200 different hMOs have been discovered and characterized, but only a few abundant hMOs can be produced in sufficient amounts to be applied in infant formula. These hMOs are usually supplied in infant formula as single molecule, and it is unknown which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…infantis and F. prausnitzii are co-cultured in the presence of 2′-FL, these bacteria grow faster in co-culture than in monocultures in the presence of 2′-FL. The in vitro results reported by Cheng et al [ 78 ] are in alignment with our observed simultaneous increase in the species B. longum and the butyrate producer F. prausnitzii in human subjects. Furthermore, our previous work and that of other groups have also demonstrated that prebiotics can simultaneously increase stool counts of Bifidobacterium and F. prausnitzii in adult subjects [ 79 , 80 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…infantis and F. prausnitzii are co-cultured in the presence of 2′-FL, these bacteria grow faster in co-culture than in monocultures in the presence of 2′-FL. The in vitro results reported by Cheng et al [ 78 ] are in alignment with our observed simultaneous increase in the species B. longum and the butyrate producer F. prausnitzii in human subjects. Furthermore, our previous work and that of other groups have also demonstrated that prebiotics can simultaneously increase stool counts of Bifidobacterium and F. prausnitzii in adult subjects [ 79 , 80 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although changes in F. prausnitzii were not noted in our in vitro experiments, an increase in Eubacterium rectale / Clostridium coocoides , other main butyrate producer group, was detected. Interestingly, Cheng et al [ 78 ] recently reported that when B. longum subsp. infantis and F. prausnitzii are co-cultured in the presence of 2′-FL, these bacteria grow faster in co-culture than in monocultures in the presence of 2′-FL.…”
Section: Discussionmentioning
confidence: 99%
“…infantis, B. longum subsp. bifidum, and B. breve strains, [37][38][39] while only certain B. longum subsp. longum strain such as B. longum subsp.…”
Section: Discussionmentioning
confidence: 96%
“…longum cannot ferment 3-FL, which was also observed in a recent study. 37 The fermentation of fucosylated hMOs by bifidobacteria is subspecies and strain specific, i.e., they were commonly utilized by B. longum subsp. infantis, B. longum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…The principles of such resistance are not fully understood, although in some Actinobacteria, spore formation similar to that in Clostridia has been described [ 49 ]. Similar to Lactobacilli , Bifidobacteria also prefer carbohydrate catabolism [ 50 ] followed by a decrease of pH in their environment, thus suppressing multiplication of competitive microbiota. Unlike Lactobacilli , Bifidobacterium can colonize the chicken caecum after a single dose administration [ 32 ].…”
Section: Novel Types Of Probiotics From Gut Microbiotamentioning
confidence: 99%